Normal limits of the electrocardiogram in Angolans - Gonçalves, MAA (2020)
Introduction. Studies on the normal electrocardiogram limits in African populations are limited, especially in sub-Saharan Africa. There is no literature describing normal ECG limits in Angolans. Objectives. The aim of this study is to establish the normal ECG limits for adult Angolans, without established heart disease, stratified by gender and age. Methods. A cross-sectional study was performed, involving 2179 participants from a population in northern Angola, without established heart disease, aged between 15 and 74 years. A 12‑lead ECG and a rhythm strip were recorded for all participants and analysed and processed by the University of Glasgow software and encoded by the Minnesota Code. The normal range of the electrocardiographic parameters were established as the 2nd and 98th percentiles of the measurement distribution per age group and gender. Mann-Whitney and Kruskal-Wallis tests were used for two independent groups and Bonferroni adjustments were used for multiple testing. GAMLSS models were used to obtain the continuous age-dependent percentile curves. Results. The normal range of the ECG differed between men and women: heart rate 49 to 100 bpm vs. 55 to 108 bpm, P wave duration 81 to 130 ms vs. 84 to 130 ms, PR interval 119 to 210 ms vs. 120 to 202 ms, QRS duration 74 to 110 ms vs. 70 to 104 ms, QT interval 324 to 441 ms vs. 314 and 438 ms, P-wave axis − 29 to 850 vs. -18 to 810, QRS-wave axis − 13 to 850 vs. -180 and 820, T-wave axis 0 to 720 vs. -8 to 730, Sokolow-Lyon index 2.13 to 6.21 mV vs. 1.60 to 4.87 mV, Cornell index 0.17 to 6.24 mV vs. 0.14 mV to 4.35 mV. Conclusions. The values described for the electrocardiographic measurements above can act as a reference framework for Angolan adults without established heart disease. Our study suggests that the normal range of most ECG parameters vary according to age and sex and the ECG diagnostic criteria must therefore be specific for these demographic measures.